Toward a New Moral Understanding of the Tudor Conquest of Ireland. Issue 3 (1st December 2019) - Palmer, William
Abstract : The English conquest of Ireland during the sixteenth century was accompanied by extreme violence. Historians remain divided on the motivations behind this violence. This article argues that the English violence in Ireland may be attributed to four main factors: the fear of foreign Catholic intervention through Ireland; the methods by which Irish rebels chose to fight; decisions made by English officials in London to not fund English forces in Ireland at a reasonable level while demanding that English officials in Ireland keep Ireland under control; and the creation of a system by which many of those who made the plans never had to see the suffering they inflicted. The troops who carried out the plans had to choose between their own survival and moral behaviors that placed their survival at risk.